Investigating the human brainstem with structural and functional MRI - Florian Beissner (Frontiers Research Topics, 2014)
The brainstem is one of the least understood parts of the human brain despite its prime importance for the maintenance of basic vital functions. Owing to its role as a relay station between spinal cord, cerebellum and neocortex, the brainstem contains vital nodes of all functional systems in the central nervous system, including the visual, auditory, gustatory, vestibular, somatic and visceral senses, and the somatomotor as well as autonomic nervous systems. While the brainstem has been extensively studied in animals using invasive methods, human studies remain scarce. Magnetic resonance imaging (MRI) as a non-invasive and widely available method is one possibility to access the brainstem in humans and measure its structure as well as function. The close vicinity of the brainstem to large arteries and ventricles and the small size of the anatomical structures, however, place high demands on imaging as well as data analysis methods. Nevertheless, the field of brainstem-(f)MRI has significantly advanced in the past few years, largely due to the development of several new tools that facilitate studying this critical part of the human brain. Within this scope, the goal of this Research Topic is to compile work representing the state of the art in functional and structural MRI of the human brainstem.